Assessment of pose repeatability and specimen repositioning of a robotic joint testing platform - El,Daou H; Lord,B; Amis,A; Rodriguez,y Baena F (MEDICAL ENGINEERING & PHYSICS, 2017)
This paper describes the quantitative assessment of a robotic testing platform, consisting of an industrial robot and a universal force-moment sensor, via the design of fixtures used to hold the tibia and femur of cadaveric knees. This platform was used to study the contributions of different soft tissues and the ability of implants and reconstruction surgeries to restore normal joint functions, in previously published literature.To compare different conditions of human joints, it is essential to reposition specimens with high precision after they have been removed for a surgical procedure. Methods and experiments carried out to determine the pose repeatability and measure errors in repositioning specimens are presented. This was achieved using an optical tracking system (fusion Track 500, Atracsys Switzerland) to measure the position and orientation of bespoke rigid body markers attached to the tibial and femoral pots after removing and reinstalling them inside the rigs. The pose repeatability was then evaluated by controlling the robotic platform to move a knee joint repeatedly to/from a given pose while tracking the position and orientation of a rigid body marker attached to the tibial fixture.The results showed that the proposed design ensured a high repeatability in repositioning the pots with standard deviations for the computed distance and angle between the pots at both ends of the joint equal to 0.1 mm, 0.01 mm, 0.13° and 0.03° for the tibial and femoral fixtures respectively. Therefore, it is possible to remove and re-setup a joint with high precision. The results also showed that the errors in repositioning the robotic platform (that is: specimen path repeatability) were 0.11 mm and 0.12°, respectively.